Technology For Developing Oral Speech Competence In General Education School Students - Y. A, Shukurov; D. M, Ubaydullayeva (Innovative Technologica: Methodical Research Journal, 2025)
Oral speech competence plays a crucial role in students' cognitive, social, and academic development. As educational paradigms shift towards communicative competence, integrating technology into language instruction presents new opportunities for enhancing students' spoken proficiency. This paper examines the role of technology in fostering oral speech competence, analyzing its implementation within general education settings. This study highlights practical applications, challenges, and the effectiveness of innovative methodologies, including AI-powered language assistants, interactive speech simulations, and gamified learning platforms.